What's wrong with using the F word? A systematic integrative review of how the fetus is talked about in situations of fetal demise or high risk of fetal loss. (December 2019) - Anolak, Helena; Thornton, Charlene; Davis, Deborah
Highlights: The 23 included studies represented the voices of women, their partners and allied health professionals. The term 'Baby' is the most widely recognised word used in instances of fetal loss and high risk of fetal demise. Gender identification- naming the fetus in utero. Medical diagnosis or terminology used to label the fetus instead of using the word fetus or baby. Euphemisms to name the fetus. Parents and health care professionals distancing themselves by using words that are non specific or not naming the fetus at all. This review contributes new insights into our understanding of the term 'fetus'. Need for further research into the way the fetus is addressed and dealt with in instances of fetal loss or high risk of fetal loss within Maternity care practices. Abstract: Background: Limited research exists that investigates the language parents and health professionals use when faced with a high-risk likelihood of fetal demise or an instance of fetal loss. This review examines the language used when referring to the 'fetus' in these cases to better understand the meaning different groups might ascribe to the fetus and how their word choice may reflect their strategies for managing in these situations. Methods: An integrative review of primary, peer-reviewed research was conducted. A systematic search of seven databases was undertaken, articles critiqued and summarised using the Preferred Reporting Items for Systemic Reviews and Meta-Analysis (PRISMA). The comprehensive process of data analysis and synthesis followed a constant comparison approach. Results: The 23 included studies represented the voices of women, their partners, obstetricians, nurses, midwives and allied health professionals. Five major themes emerged with the main finding being that the term 'Baby' is the most widely recognised word used in instances of fetal loss and high risk of fetal demise. Conclusion: History, science and law all influence how the fetus is understood and discussed within society. This review contributes new insights into our understanding of the term 'fetus' emphasizing the need for further research into the way the fetus is addressed and dealt with in instances of fetal loss or high risk of fetal loss within Maternity care practices.